1988
DOI: 10.1017/s0043174500075184
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Fate of Dicamba, Picloram, and Triclopyr in Horsenettle,Solanum carolinense

Abstract: Greenhouse studies were conducted to determine the extent of translocation from the foliage to fleshy roots, the inherent toxicity, and the fate of radiolabeled and nonlabeled dicamba, picloram, and triclopyr in horsenettle. Roots of horsenettle acted as the major sink for photosynthate accumulation at the 0.2- to 0.5-bloom growth stages as determined by autoradiography. Dicamba, picloram, and triclopyr were translocated into the roots of horsenettle and accumulation continued for at least 16 days.14C associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…Previous research has shown picloram and 2,4-D conjugates remain stable at least 3 to 4 months when frozen. 5 Herbicides and metabolites were extracted by grinding in 80% ethanol:water (v/v) in a motor-driven tissue homogenizer, followed by centrifugation and re-extraction of the pellet twice in the same solvent mixture to increase recovery. The extracts were combined and extracted with ether once.…”
Section: Metabolismmentioning
confidence: 99%
“…Previous research has shown picloram and 2,4-D conjugates remain stable at least 3 to 4 months when frozen. 5 Herbicides and metabolites were extracted by grinding in 80% ethanol:water (v/v) in a motor-driven tissue homogenizer, followed by centrifugation and re-extraction of the pellet twice in the same solvent mixture to increase recovery. The extracts were combined and extracted with ether once.…”
Section: Metabolismmentioning
confidence: 99%
“…The efficacy of control of horsenettle depends on the ability to control the vigorous root system of the plant (Gorrell et al . 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, effective translocated herbicides for horsenettle root systems are auxin‐based (e.g. triclopyr) (Gorrell et al . 1978, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, effective translocated herbicides for horsenettle root systems are auxin-based (e.g. triclopyr) (Gorrell et al 1978(Gorrell et al , 1988. Therefore, the elucidation of the endogenous morphological control of the root system in relation to auxin is important, both to improve weed control efficacy and to solve general physiological questions regarding root development.…”
Section: Relationship Between Root Morphology and Vegetative Reproducmentioning
confidence: 99%